Synthesis and characterization of GdVO4 nanoparticles by a malic acid-assisted sol-gel method - Chumha N. (Elsevier, 2014)
GdVO4 powders were synthesized by a sol-gel method using malic acid as a chelating agent, followed by calcinations at 300-700 °C for 3 h. The products characterized by FTIR, XRD, SEM and TEM, revealed that purity, crystallinity and particle sizes of tetragonal GdVO4 nanoparticles increased with increasing calcination temperatures. The stoichiometry of the GdVO4 powders was confirmed using EDS. The photocatalytic activities of the GdVO4 powders were evaluated by studying the degradation of rhodamine B (RhB) in an aqueous solution. © 2014 Elsevier B.V.